2020
DOI: 10.3390/ma13061465
|View full text |Cite
|
Sign up to set email alerts
|

Sound Absorption Performance of the Poplar Seed Fiber/PCL Composite Materials

Abstract: Composite materials were prepared by the hot pressing method using poplar seed fibers and polycaprolactone (PCL) as the raw materials to solve the problems related to the recycling of waste fibers. The effects of mass fraction of poplar seed fibers, the volume density, and thickness on the sound absorption performance of the resulting composite materials were studied. The sound absorption coefficient curves of the composite material were obtained by the acoustic impedance transfer function method. The sound ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The FCNS-5 and FCNS-18 showed good high-frequency and low-frequency sound absorption, respectively. Notably, the absorption coefficient of sandwiched FCNSs always outperformed that of the FCNS-5 and FCNS-18 in almost all frequency bands from 63 to 6300 Hz 12,27 (see Supplementary Methods), and the NRC of sandwiched FCNSs achieved 0.56, satisfying the requirement of high-efficiency sound absorption materials (NRC ≥ 0.56) 63 , whereas the values for FCNS-5 and FCNS-18 were only 0.40 and 0.32, respectively. Additionally, the design values of sound absorption coefficients of sandwiched FCNSs were also calculated based on the above-mentioned JCA module, and a detailed comparison between experimental values and designed values is described in Supplementary Discussions.…”
Section: Resultsmentioning
confidence: 74%
“…The FCNS-5 and FCNS-18 showed good high-frequency and low-frequency sound absorption, respectively. Notably, the absorption coefficient of sandwiched FCNSs always outperformed that of the FCNS-5 and FCNS-18 in almost all frequency bands from 63 to 6300 Hz 12,27 (see Supplementary Methods), and the NRC of sandwiched FCNSs achieved 0.56, satisfying the requirement of high-efficiency sound absorption materials (NRC ≥ 0.56) 63 , whereas the values for FCNS-5 and FCNS-18 were only 0.40 and 0.32, respectively. Additionally, the design values of sound absorption coefficients of sandwiched FCNSs were also calculated based on the above-mentioned JCA module, and a detailed comparison between experimental values and designed values is described in Supplementary Discussions.…”
Section: Resultsmentioning
confidence: 74%
“…When the density was less than 172 kg/m 3 , with the increase in the density of the composites, the number of micropores in the composites with the same thickness increased, thus improving the sound-absorption properties of the composites. However, with the increased density of the composites, the pore size and number of micropores in the composites decreased, which reduced the friction and vibration between the air and fibers in the composites, thus reducing the consumption of sound energy and the sound-absorption properties [18]. According to the above analysis in Figure 5, the density of 172 kg/m 3 was the best process parameter.…”
Section: Influence Of Density Of Composites On Sound-absorption Propertiesmentioning
confidence: 94%
“…The I variant generally showed that the tested materials could not be classified as sound absorber materials since their NRC values were less than 0.2, as specified in [29,30]. The second variant (II) results showed the greatest sound reduction compared to the other variants.…”
Section: Noise Reduction Properties Comparisonmentioning
confidence: 98%
“…A sound-absorption material is generally required to have a noise reduction coefficient (NRC) value greater than or equal to 0.20. Practically useful materials have an NRC higher than 0.4, while materials with an NRC greater than 0.56 are referred to be high-efficiency sound-absorbing materials [3,29,30]. The amount of reflected sound waves from the tested surface are presented in percentages.…”
Section: Noise Reduction Properties Comparisonmentioning
confidence: 99%